The role of AI and digital technologies in higher education - Alla F. Matuszak; Olga Yu. Pavlova; Ludmila S. Nosova; Leyla F. Velieva; Irina M. Salimova (Russian Journal of Education and Psychology, 2025)
Background. In the context of digitalization of all spheres of life, the issue of using digital technologies and artificial intelligence in education is becoming especially relevant. The effectiveness of using technologies in a university largely depends on how much the opinions of students and teachers coincide when choosing them.